Stabilitas Transien pada Saluran Transmisi dengan Static VAR Compensator (SVC) dan PSS (Power System Stabilizer) - Zainal Abidin (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2020)
In this discussion the modeling of a transmission system consisting of multiple machine. To maintain transient stability and reduce the oscillation of the system SVC and PSS are used. In its operation, the electric power system often experiences short circuit, both permanent and temporary. The short circuit interruption can cause deviations in electric power system variables, such as voltage, frequency, and others. This deviation can affect the stability of the electric power system. Stability in an electric power system is defined as the ability of an electric power system to maintain synchronization during interruptions as well as after disruptions occur.PSS performance is expanding the stability limits of the electric power system by providing synchronous engine rotor oscillation reduction through generator excitation. This damping is provided by the electric torque applied to the rotor in accordance with variations in speed.With Matlab/Simulink, we can examine the role of PSS and SVC in the process of reducing oscillations, changes in rotor angle and engine speed. PSS and SVC can do the damping process quickly from disturbance to stable conditions.